2022
DOI: 10.5056/jnm21122
|View full text |Cite
|
Sign up to set email alerts
|

Role of Peroral Endoscopic Myotomy in Advanced Achalasia Cardia With Sigmoid and/or Megaesophagus: A Systematic Review and Metanalysis

Abstract: Background/AimsSigmoid esophagus and/or megaesophagus are considered as an advanced stage in the natural history of achalasia cardia. The role of peroral endoscopic myotomy (POEM) in these subset of patients is emerging. We performed a systematic review and metanalysis to study the efficacy of POEM in advanced achalasia cardia with sigmoid and megaesophagus. MethodsA literature search in PubMed and Embase was done from inception till August 3, 2021 to look for studies reporting exclusively on the role of POEM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…ПОЭМ может быть выполнен при при любом типе ахалазии в том числе при его S-образной деформации (IV стадия по классификации Б. В. Петровского) [5,12,19,20]. При этом технический успех операции и клиническое улучшение возникает более чем у 85% пациентов.…”
Section: Discussionunclassified
“…ПОЭМ может быть выполнен при при любом типе ахалазии в том числе при его S-образной деформации (IV стадия по классификации Б. В. Петровского) [5,12,19,20]. При этом технический успех операции и клиническое улучшение возникает более чем у 85% пациентов.…”
Section: Discussionunclassified
“…POEM provides more effective and long-lasting relief for type III achalasia and should be considered a first-line treatment for this challenging sub-type [39,40]. In addition, POEM has good clinical efficacy and morphological improvement in treating patients with advanced achalasia With Sigmoid or Megaesophagus [41,42]. Furthermore, prior PD and LHM may make subsequent POEM treatment more challenging, but it does not impede successful POEM implementation and the safety and efficacy of achalasia patients [43,44].…”
Section: Particular Achalasia Patients and Other Esophageal Motility ...mentioning
confidence: 99%
“…d. POEM is technically feasible option, but clinical success is less compared to common achalasia patients. e. A systematic review from 2022 65 concluded that POEM appears to be an effective modality of treatment for advanced sigmoid or megaesophagus achalasia, but a very high incidence of reflux esophagitis is seen already less than 2 years after procedure. It seems that they did not give any importance to this complication that may produce severe adverse effects.…”
Section: Poem For End-stage Achalasiamentioning
confidence: 99%